Preoperative hypoalbuminemia and severe acute malnutrition as prognostic factors for postoperative complications in major abdominal surgery: A single-center retrospective study - Haloho, Lestarina Veronica; Nurnaningsih, Nurnaningsih; Paryanto, Endy (Paediatrica Indonesiana, 2023)
Background Hypoalbuminemia and malnutrition are common factors that can adversely affect wound healing and increase the risk of postoperative infections. Improvements in albumin and preoperative nutritional status are expected to reduce the incidence of complications following postoperative abdominal surgery. Objective To evaluate the roles of hypoalbuminemia and poor preoperative nutritional status as prognostic factors for postoperative complications in pediatric patients undergoing major abdominal surgery. Methods This retrospective cohort study included pediatric patients aged 1 month to 18 years who underwent major abdominal surgery and were treated in the pediatric intensive care unit (PICU) of Dr. Sardjito Hospital between January 1, 2017 to December 31, 2021. The primary was the incidence of postoperative complications within 14 days after the surgical procedure. Results Out of the 201 pediatric patients included in the study, 54.7% were male. We observed an overall complication rate of 21.3% following abdominal surgery, with sepsis as the most frequent, affecting 14.9% of the cases. On average, postoperative complications occurred approximately 10.9 days after surgery. Multivariate analysis identified severe acute malnutrition [hazard ratio (HR) 2.09 (95%CI 1.01 to 4.33); P=0.047], preoperative hypoalbuminemia of >2.5 to 3.0 g/dL [HR 3.64 (95%CI 1.57 to 8.41); P=0.003], preoperative hypoalbuminemia ?2.5 g/dL [HR 3.1 (95%CI 1.11 to 8.64); P=0.03], and age <1 year [HR 2.16 (95%CI 1.09 to 4.11); P=0.026] as significant prognostic factors for post-abdominal surgery complications in children. Conclusion Preoperative severe acute malnutrition and preoperative hypoalbuminemia of ?3 g/dL are significant prognostic factors for the occurrence of postoperative complications in pediatric patients undergoing abdominal surgery. Infants less than one year of age are at increased risk of such complications.